Computational modelling of hard polyethylene precast panel for temporary supporting of tunnel - Khalajmasoumi, Mohammad (2013)
In the past few decades, underground railway transportation system has become necessary in crowded cities due to the increase in population. Therefore, it is vital to develop an advanced construction method to speed up the construction of tunnels. Using Sprayed Concrete (SC) as temporary support during the construction process is known as traditional method for tunnels construction. SC has some disadvantages during implementation such as tough preparation and installation. It is also a time consuming procedure. Therefore, the use of new construction material is needed to design and replace the conventional SC structure. This study was carried out to investigate the use of hard polymer material as precast panel for temporary support of tunnels. For this reason, Hard Density Polyethylene (HDPE) polymer was selected due to its particular mechanical features and commercial specifications. Experimental tests of compression, tension, and flexural were carried out to determine the material properties and mechanical behaviour of HDPE polymer. Further analyses were then carried out to determine the mechanics of polymer materials to be selected as an appropriate hyperelastic form to model the HDPE polymer. From the analysis, YEOH model was selected and utilised in the Finite Element Analysis (FEA) using ABAQUS 6.9EF. Explicit Dynamic (ED) procedure anad analysis was used to simulate the hyperelastic deformation of HDPE polymer structures. The mathematical model and computational procedure were validated by comparing the simulation results of a three-dimensional (3D) model of HDPE under compression and flexural load with the experimental results in terms of load-deflection relationship and Strain Energy Potential. The comparison and validation of the model show 1.6% and 1.0% Mean Percentage Error for compression and flexural result, respectively. Furthermore, it shows 8% overall error (NRMSD) for compression and 13.90% difference for flexural. The established simulation procedure was then applied on the proposed model of curvature HDPE polymer structure for temporary supports of tunnels. The actual loading and boundary conditions of the tunnel were applied on the FEA model and analysed using the ED procedure. The flexural strength response of the structure was plotted as load-deflection curve to show the stiffness that can be tolerated by the curvature structure. The HDPE is a hyperelastic material with non-linear behaviour where the curve of the stress-strain in tensile and flexural was similar to that of metals. The results illustrate the advantages and disadvantages of the possibility of utilising polymer materials during the tunnel construction process. In the simulation of the precast panel using actual dimension, 20 mm displacement was applied on the HDPE precast panel with 5 mm/min loading rate. HDPE precast panel with basic geometry (without web and stiffener) tolerated almost 5.76 kN strength with specific displacement (20 mm) which is equal to 1 MPa. This value is less than adequate strength for temporary support, however it can be improved by geometry modification of HDPE precast panel.